Who believes in me? The effect of student-teacher demographic match on teacher expectations - Seth Gershenson; Stephen B. Holt; Nicholas Papageorge (W.E. Upjohn Institute for Employment Research, 2015)
Teachers are an important source of information for traditionally disadvantaged students. However, little is known about how teachers form expectations and whether they are systematically biased. We investigate whether student-teacher demographic mismatch affects high school teachers' expectations for students' educational attainment. Using a student fixed effects strategy that exploits expectations data from two teachers per student, we find that nonblack teachers of black students have significantly lower expectations than do black teachers. These effects are larger for black male students and math teachers. Our findings add to a growing literature on the role of limited information in perpetuating educational attainment gaps.
Keywords: I24; D84; J15; J16; 330; Educational Attainment; Expectations; Stigmatization; Mismatch